Developing Resilience and Independence Among Female Students In A Pesantren-Based University: A Qualitative Case Study - Siti Yulia Rahmah; Putri Roofi Salikin; Haliza Nur Azkia; Syarifah; Ihwan Mahmudi (CV Putra Publisher, 2026)
This study explores the development of resilience and independence among female students at Universitas Darussalam Gontor, a pesantren-based higher education institution. A qualitative case study approach was employed involving 18 participants, including institutional leaders, lecturers, dormitory supervisors, and female students. Data were collected through semi-structured interviews, participant observation, and document analysis and were analyzed using reflexive thematic analysis. The findings indicate that resilience and independence are developed through five interconnected dimensions: spirituality, discipline, organizational engagement, dormitory life, and social support. Spirituality and discipline strengthen emotional regulation, perseverance, and adaptive coping, which support students' resilience. Meanwhile, organizational participation and dormitory life foster independence by enhancing responsibility, leadership, communication, and decision-making skills. Supportive relationships among lecturers, dormitory supervisors, and peers further create a psychologically safe learning environment that reinforces both resilience and independence. The findings suggest that, within the context of Universitas Darussalam Gontor, the integration of Islamic values, character education, and communal living contributes to the development of female students' resilience and independence.